Kajian Komprehensif tentang Hakikat, Fungsi, dan Proses Penelitian Ilmiah - Ta’wil, Ta’wil; Ondeng, Syarifuddin; Mustami, Khalifa (Journal of Health, Education, Economics, Science, and Technology, 2025)
Research serves as the fundamental basis for the development of scientific knowledge and the resolution of problems across various aspects of life. This article provides a comprehensive discussion on the nature, functions, and processes of research. The nature of research is understood as a systematic, methodological, and objective effort to discover or validate scientific knowledge. The functions of research are not limited to the advancement of science, but also include problem-solving, improving the quality of public policy, and fostering innovation. Meanwhile, the research process involves several essential stages, including problem identification, literature review, formulation of hypotheses or research questions, data collection and analysis, and drawing conclusions. By understanding these three aspects, research can be conducted in a more directed, valid, and practically beneficial manner for the advancement of science and societal well-being.